Human adaptability - Moran, Emilio F., author.
1 online resource
Keywords: Designed to help students understand the multiple levels at which human populations respond to their surroundings, this essential text offers the most complete discussion of environmental, physiological, behavioral, and cultural adaptive strategies available. Among the unique features that make Human Adaptability outstanding as both a textbook for students and a reference book for professionals are a complete discussion of the development of ecological anthropology and relevant research methods; the use of an ecosystem approach with emphasis on arctic, high altitude, arid land, grassland, tropical rain forest, and urban environments; an extensive and updated bibliography on ecological anthropology; and a comprehensive glossary of technical terms. - There is enhanced emphasis throughout on the role of gender in human adaptability research and on global environmental change as it affects particular ecosystems. - Students are guided to websites that provide access to relevant material, complement the text's coverage of biomes, and suggest ways to become active in environmental issues. - The fourth edition includes updated material on climate change and environmental policy. This book is essential reading for students undertaking courses inenvironmental anthropology and human ecology.